Differential yoke-aerofin thrust vector control system - VOIGT; CHE-RAM S; SPEICHER; JOHN M; VOIGT; ALLAN A (1997)
An actuation system for controlling the steerable nozzle of a missile or like vehicle is combined with an aerofin control system, both of which are driven in unison by associated drive motors and gear assemblies, one set for each aerofin. The nozzle steering system comprises two essentially identical yoke plates mounted along a plane generally transverse to the missile axis and oriented orthogonally relative to each other about the missile axis for pivoting the nozzle through mutually orthogonal axes, thereby achieving omni-directional steering. The yoke plates are coupled at opposite ends to pinion gears which are driven by the same gear assemblies which drive the associated aerofins. The arrangement permits common directional control of the steerable nozzle and the aerofins while maintaining the nozzle in a neutral direction when the aerofins are rotated to a missile roll control mode.